Hubungan antara Kegiatan Literasi dengan Minat Anak Membaca Buku Pelajaran Agama Islam dalam Keluarga di Kelurahan Tobekgodang Pekanbaru - Azwir Salam (Departement of Mathematics Education, 2023)
The 2013 Curriculum Policy contains literacy activities. At present literacy activities have been carried out in most schools marked by the majority of students bringing non-lesson books from home to school to read when literacy activities take place. It is suspected that literacy activities can foster students' interest in reading. This study aims to see the relationship between literacy activities and children's interest in reading Islamic religious textbooks in the family in the Tobekgodang Village, Pekanbaru. This study uses a correlational research method. The population in this study were children who studied at SMP/MTs and SMA/SMK/MA who were domiciled in Tobekgodang Village, Pekanbaru. The sample in this study is children who live in RW 013, totaling 45 people. Data collection techniques using questionnaires, observation, and documentation. The analysis technique uses the contingency coefficient. The results of this study indicate that there is a significant relationship between literacy activities and an interest in reading Islamic Religion textbooks in the family in Tobekgodang Village, Pekanbaru